2016
DOI: 10.1002/2016jf003993
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Davies and McSaveney on “The reduction of friction in long runout landslides as an emergent phenomenon”

Abstract: Key Points We reply to comment by Davies and McSaveny We argue that we cannot comment on the role of fragmentation Our work has demonstrated a friction reduction mechanis that does not involve fragmentation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Analogously, the increased fragmentation for the geometry and volume series causes attenuated seismic efficiency (Figure 12), indicating that the inelastic process associated with viscous damping, friction and irreversible deformation during fragmentation consumes a significant amount of impact energy. As a consequence, these results agree well with the hypothesis that fragmentation is an energy-consuming process (Campbell, 1990;Collins & Melosh, 2003;Crosta et al, 2007;Hungr, 2006;Johnson et al, 2016;Locat et al, 2006).…”
Section: Implicationsupporting
confidence: 90%
See 1 more Smart Citation
“…Analogously, the increased fragmentation for the geometry and volume series causes attenuated seismic efficiency (Figure 12), indicating that the inelastic process associated with viscous damping, friction and irreversible deformation during fragmentation consumes a significant amount of impact energy. As a consequence, these results agree well with the hypothesis that fragmentation is an energy-consuming process (Campbell, 1990;Collins & Melosh, 2003;Crosta et al, 2007;Hungr, 2006;Johnson et al, 2016;Locat et al, 2006).…”
Section: Implicationsupporting
confidence: 90%
“…This hypothesis has been accepted (e.g., Bowman et al, 2012;Imre et al, 2010) but also contradicted (e.g., Haug et al, 2016;Hungr, 2006). An important reason for opposing this hypothesis is that dynamic fragmentation is expected to be an energy-consuming process (Campbell, 1990;Collins & Melosh, 2003;Hungr, 2006;Johnson et al, 2016). Based on data from 9 rock avalanche investigations, Locat et al (2006) suggested that fragmentation depends on the potential energy and rock mass strength, and no clear relationships were found between fragmentation and mobility.…”
mentioning
confidence: 99%
“…Recent studies of debris avalanches have indicated the necessity of the normal stress reduction in debris avalanches (Pudasaini & Miller, 2013), which is also supported by experimental (R H Iverson, 1997;R M. Iverson & Vallance, 2001) and numerical (Gueugneau et al, 2017;Iverson et al, 2015;Lucas et al, 2014) studies. Nevertheless, this is currently the source of active debate (Davies & McSaveney, 2016;Iverson, 2016;Johnson et al, 2016aJohnson et al, , 2016bJohnson et al, , 2016c.…”
Section: Discussionmentioning
confidence: 99%